The Effectiveness of the CERDAS Learning Media in STEAM-Integrated PjBL to Enhance Elementary Students’ Critical Thinking and Collaboration Skills - Chitra Sintarani; Woro Sumarni; Bambang Subali (Universitas Negeri Semarang, 2026)
The achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 7 (Affordable and Clean Energy), requires innovative science learning that develops students’ critical thinking and collaboration skills while fostering awareness of renewable energy and environmental sustainability. However, science learning in elementary schools is often dominated by teacher-centered instruction, limiting students’ opportunities to engage in authentic problem-solving and collaborative activities. This study aimed to examine the effectiveness of the CERDAS learning media (Creating Eco-Friendly Electronic Devices Powered by Solar Energy), implemented through a STEAM-integrated Project-Based Learning (PjBL) approach, in enhancing the critical thinking and collaboration skills of fifth-grade students. The study employed a pre-experimental one-group pretest-posttest design involving 30 fifth-grade students from SD Negeri Sambiroto 02, Semarang City, Central Java, Indonesia. Data on critical thinking skills were collected through pretests and posttests, while collaboration skills were assessed using observation sheets and project evaluation rubrics. The results revealed that students’ critical thinking scores increased from 53.00 to 86.67, with an N-Gain score of 0.72, categorized as high. Students’ collaboration scores also improved from 24.33 to 51.50, with an N-Gain score of 0.76, indicating a high level of improvement. Furthermore, the paired sample t-test yielded a significance value of 0.000 (p < .001), confirming that the improvements were statistically significant. These findings suggest that the CERDAS learning media is an effective innovation for transforming elementary science education by enhancing students’ critical thinking and collaboration skills while supporting renewable energy literacy and sustainability awareness in line with the Sustainable Development Goals.